2016
DOI: 10.1242/dev.134189
|View full text |Cite
|
Sign up to set email alerts
|

Dental mesenchymal stem cells

Abstract: Mammalian teeth harbour mesenchymal stem cells (MSCs), which contribute to tooth growth and repair. These dental MSCs possess many in vitro features of bone marrow-derived MSCs, including clonogenicity, expression of certain markers, and following stimulation, differentiation into cells that have the characteristics of osteoblasts, chondrocytes and adipocytes. Teeth and their support tissues provide not only an easily accessible source of MSCs but also a tractable model system to study their function and prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
235
0
10

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(245 citation statements)
references
References 59 publications
0
235
0
10
Order By: Relevance
“…They differentiate into the pulp cells and odontoblasts that form dentin as the tooth grows, in coordination with the epithelial cells. Previous studies have shown that peripheral nerve-associated glial cells can also serve as mesenchymal stem cells for maintaining incisor pulp tissue homeostasis and repair (Kaukua et al, 2014), with these dental mesenchymal stem cells offering potential clinical applications (reviewed by Sharpe, 2016).…”
Section: Dental Stem Cells and The Transition From Crown To Root Devementioning
confidence: 99%
“…They differentiate into the pulp cells and odontoblasts that form dentin as the tooth grows, in coordination with the epithelial cells. Previous studies have shown that peripheral nerve-associated glial cells can also serve as mesenchymal stem cells for maintaining incisor pulp tissue homeostasis and repair (Kaukua et al, 2014), with these dental mesenchymal stem cells offering potential clinical applications (reviewed by Sharpe, 2016).…”
Section: Dental Stem Cells and The Transition From Crown To Root Devementioning
confidence: 99%
“…MSCs can be obtained from not only bone marrow but also medical wastes such as adipose tissue [57,58], umbilical tissue [59][60][61][62], and dental pulp [63]. MSCs are positive for the common markers CD73, CD90, and CD105; however, they are negative for the endothelial marker CD31 and hematopoietic marker CD45 [56,64].…”
Section: Mscsmentioning
confidence: 99%
“…Mesenchymal stromal cells (MSCs) are multipotent progenitors derived from different sources, including bone marrow (BM) , adipose tissue ( Van Pham et al, 2014), umbilical cord (UC) blood (Sibov et al, 2012), UC (Van Pham et al, 2016), Wharton's jelly (Ducret et al, 2016), and other tissues (Ducret et al, 2016;Pelekanos et al, 2016;Sharpe, 2016). Although, bone marrow-derived MSCs (BMMSCs) are a popular source of MSCs for research and clinical applications, there are now alternative sources of MSCs, including adipose tissue-derived stem cells (ADSCs) and umbilical cord-derived mesenchymal stem cells (UCMSCs).…”
Section: Introductionmentioning
confidence: 99%